The larval attachment organ of the tropical gar Atractosteus tropicus Gill, 1863 (Lepisosteiformes: Lepisosteidae). Issue 2 (13th April 2021) - Pinion, Amanda K.; Siegel, Dustin S.; Britz, Ralf; Martínez‐García, Rafael; Álvarez‐González, Carlos A.; Conway, Kevin W.
Abstract: Larval attachment organs (LAOs) are unicellular or multicellular organs that allow larvae to adhere to a substrate before yolk‐sac absorption and the free‐swimming stage. This study documents the LAO of tropical gar, Atractosteus tropicus, using a combination of scanning electron microscopy and light microscopy. It is shown that the LAO of A. tropicus is a super‐organ surrounded by a wall and containing at its centre many smaller multicellular organ units, each comprised of attachment and support cells. Attachment cells are secretory and house large vacuoles filled with a glycoprotein. At hatching, the super‐organ is well developed and occupies almost the entire anteroventral surface of the head. During subsequent development, the smaller individual units begin to regress, until at 6 days post‐hatching the super‐organ and its individual units are no longer visible.